Message from Malaga - MacInnes, Helen, 1907-1985. (New York : Harcourt Brace Jovanovich, 1971)
Before Ian Ferrier left for his vacation he would not have believed his reunion with a trusted friend would result in murder, or that he would hold the key to expose a vicious conspiracy for assassination, or that he would be plunged into a desperate pursuit in which he was as much the hunted as the hunter.
Keywords: Adventure -- Fiction. -- Spain